Arginine methylation of FOXP3 is crucial for the suppressive function of regulatory T cells. (February 2019) - Kagoya, Yuki; Saijo, Hiroshi; Matsunaga, Yukiko; Guo, Tingxi; Saso, Kayoko; Anczurowski, Mark; Wang, Chung-Hsi; Sugata, Kenji; Murata, Kenji; Butler, Marcus O.; Arrowsmith, Cheryl H.; Hirano, Naoto
Abstract: Forkhead box transcription factor 3 (FOXP3) plays a pivotal role in the suppressive function of regulatory T cells. In addition to mRNA levels, FOXP3 activity can also be controlled by posttranslational mechanisms, which have not been studied in a comprehensive manner. Through extensive screening using selective inhibitors, we demonstrate that the inhibition of type I protein arginine methytransferases (PRMTs) attenuates the suppressive functions of regulatory T cells. FOXP3 undergoes methylation on arginine residues at positions 48 and 51 by interacting with protein arginine methyltransferase 1 (PRMT1). The inhibition of arginine methylation confers gene expression profiles representing type I helper T cells to FOXP3 + T cells, which results in attenuated suppressive activity. A methylation-defective mutant of FOXP3 displays less potent activity to suppress xenogeneic graft-versus-host disease in vivo . These results elucidate an important role of arginine methylation to enhance FOXP3 functions and are potentially applicable to modulate regulatory T cell functions. Highlights: Inhibiting arginine methyltransferases attenuates regulatory T cell functions. FOXP3 is arginine-methylated on R48 and 51 by interacting with PRMT1. Arginine methylation in FOXP3 is crucial for its transcriptional activity.